2014
DOI: 10.11114/jets.v2i2.261
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Technological Pedagogical Content Knowledge Self-Efficacies

Abstract: The aim of this study was to determine teachers' views on technological pedagogical content knowledge (TPACK), their self-efficacy, and whether these views changed according to sex, age, period of service, faculty graduated from, branch, access to the internet, the use of technology level, and access to in-service training which is oriented to the use of technology. Teachers' self-efficacies which are oriented to TPACK and its sub-dimensions known as technological knowledge (TK), content knowledge (CK), pedago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 21 publications
8
46
0
9
Order By: Relevance
“…From the profile obtained age is one of reasons influencing teachers' competence in technology mastery. It is in line with Kazu and Erten's finding which shows that there is a significant relation between age and TK (Kazu and Erten, 2014). Generally, getting older makes teachers more unfamiliar with the use of various technologies.…”
Section: Technological Pedagogical and Content Knowledge (Tpack)supporting
confidence: 79%
“…From the profile obtained age is one of reasons influencing teachers' competence in technology mastery. It is in line with Kazu and Erten's finding which shows that there is a significant relation between age and TK (Kazu and Erten, 2014). Generally, getting older makes teachers more unfamiliar with the use of various technologies.…”
Section: Technological Pedagogical and Content Knowledge (Tpack)supporting
confidence: 79%
“…There are several studies which demonstrated that gender had no significant effect on the level of TPACK (Ünal Bozcan, 2010;İşigüzel, 2014;Kaya et al, 2011;Şimşek et al, 2013;Kula, 2015). However, a few studies which found that TPACK levels vary depending on gender also exist in the literature (Argon et al, 2015;Tuncer & Bahadır, 2016;Kazu & Erten, 2014). Considering this situation, it may be argued that an in-depth study should be undertaken on gender to clarify the relationship between gender and TPACK levels, and check the possible factors that lead to different results.…”
Section: To What Extent Does Pre-service English Teachers' Tpack Levementioning
confidence: 99%
“…Some studies also showed that gender does not lead to a significant change in the level of TPACK (Ünal Bozcan, 2010;İşigüzel, 2014;Kaya, Özdemir, Emre, & Kaya, 2011;Kula, 2015). However, in the literature, there are a few studies which found that TPACK levels vary depending on gender (Argon et al, 2015;Tuncer & Bahadır, 2016;Kazu & Erten, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies conducted on ICT have emphasized that both gender (Keser et al, 2015;Sezer, 2015), and experience (Kazu and Erten, 2014) are important factors for the development of self-confidence. Shashaani and Khalili (2001) reported that the rate of ICT use increases as selfconfidence levels increase.…”
Section: Introductionmentioning
confidence: 99%